Evolution of the PRC's military doctrine and its implications for China's army building. - Suen, Gwo Sheng. (2008)
In the past few decades, the People's Republic of China (PRC) continues to change its military doctrine in response to changes in the international and domestic environments. And whenever there is a change in its security environment, the PRC also changes its principles of military buildup.